Verbal or Written? The Impact of Apology on the Repair of Trust: Based on Competence- vs. Integrity-Based Trust Violation - Gao, Shuhong; Yan, Jinzhe (Frontiers in Psychology, 2022)
This study examined the effect of verbal and written apologies on trust repair based on competence and integrity after a trust violation. Through three experiments, the empirical results showed that the written apology was more effective than verbal ones a restoring trust for integrity-based trust violations. However, the verbal apology was more effective against competency-based trust violations than a written one. Moreover, the results also showed that perceived trustworthiness played a mediating role between trust violation and trust repair, while positive emotions played a moderating role. Finally, this study provided the general discussion, implications, and suggestions for future research.